Ethnobotanical Study of Poisonous Plants Described by Traditional Herbal Practitioners from Narok County - Kamau , Loice N. (African Journal of Education,Science and Technology (AJEST), 2021)
Traditional medicine has remained first line of treatment to many communities in Africa. However, there are several plants that are known to cause poisoning to both animals and humans. Knowledge of such plants among traditional herbal practitioners is significant in avoiding adulteration of herbal medicine during preparation. Worldwide, many hospital visits, physiological disorders and deaths related to poisoning are caused by plant toxicity. The study sought to document toxic plants in Narok County known to traditional herbal practitioners (30). They were purposively sampled and interviewed using pilot tested questionnaires. They provided information about plants that are toxic to both animals and humans, plants that cause side effects when taken in very large dosages singly or in combination and methods of counteracting plant toxicity. A total of 26 plants were identified, family Euphorbiaceae and Asteraceae had the highest number of toxic plants cited. The most mentioned toxic plants included; Ricinus communis (8), Euphorbia candelabrum (7) and Acokanthera schimperi (7). Concerning plant toxicity related to overdosage, the traditional herbal practitioners mentioned Senna didymobotrya (5), Warbugia ugadensis (4) and Zanthozylum usambarense (4) as the most known. They also reported several plants that were used to neutralize plant toxicity; mainly, Prunus africana, Toddalia asiatica, Rhus natalensis and Rhamnus staddo. The study concluded that traditional herbal practitioners of Narok County have a rich knowledge of toxic plants. Further investigations are recommended to authenticate safety and efficacy of combination therapy that included toxic plants.